Pengaruh Aspek Keuangan dan Financial Technology pada Warung Mie Gacoan - Mustafida, Mustafida (Program Studi Hukum Ekonomi Syariah, 2024)
Mie Gacoan is a very famous place to eat in Indonesia which is one of the businesses that is growing rapidly and has considerable growth potential today. There have been many business actors who have profited from this culinary business. However, not a few culinary business actors have gone out of business, aka bankrupt, because the marketing strategies used are not appropriate and the quality of service is not optimal. This means the success of a culinary business in managing financial aspects, the use of financial technology, and applicable business ethics. The research method used is quantitative associative with data collection carried out through national data observation. Data analysis using multiple linear regression shows that financial aspects and financial technology have a significant influence on the performance of Mie Gacoan. With a price per portion of Rp. 13,000, the profit is 21%. Sales increased by 11% annually, and for operations increased by 3%. Employee salary is 3%. The cost of raw materials has also increased by 6% every year.